The Effect Of Liquidity And Solvency On Profitability In Food And Beverage Companies - Kurniawan, Andrie (Sean Institute, 2024)
This research aims to analyze the financial performance of three large companies in the food and beverage industry listed on the Indonesia Stock Exchange, namely PT. Mayora Indah Tbk (MYOR), PT. Indofood Sukses Makmur Tbk (INDF), and PT. Garudafood Putra Putri Jaya Tbk (GOOD), during the 2019-2023 period. This analysis uses various financial ratios, including liquidity, solvency and profitability ratios, to provide a comprehensive picture of how each company manages their finances in the face of intense industry competition. The research results show that MYOR has better performance in terms of liquidity and cash management compared to INDF and GOOD. However, all three companies face significant challenges in achieving optimal profitability, with Return on Investment (ROI) and Return on Equity (ROE) well below industry standards. Further regression analysis shows that the tested liquidity and solvency variables do not have a significant influence on profitability, indicating the need for a more effective financial strategy. These findings underscore the importance for companies to improve the efficiency of asset and equity management and manage debt more strategically to support long-term sustainability and competitiveness.